Homicide clearances - Regoeczi, Wendy C. (Routledge handbook of homicide studies, 2024)
Homicide clearances reflect the closing or solving of a case by arrest or exceptional means, and the rate with which homicide cases are cleared is an important metric of police productivity. Homicide clearances in the United States from 1960 to 2020 reflect a remarkable overall declining historical trend which is important for several reasons relating to deterrence and the certainty of apprehension combined with the swiftness with which that arrest takes place, closure for victims’ families and other surviving victims that provides victims a sense of justice and the opportunity to heal and move forward, but assures the larger community that killers are no longer on the loose. Homicide case clearances can be interpreted as a proxy measure for faith and confidence in police; thus, clearances promote community collaborations that are necessary for public safety and crime control to be effective. For these reasons, police practices in responding to not only homicide but other crimes as expressed in successful efforts to clear such crimes are critical for understanding public safety and security across the communities that police aim to serve and protect.